UNIVERSITY NOTES. (The Accounting Review, 1929)
Abstract The article presents information about various universities. Mr. H.A.C. Ross has left the department this year and Mr. A R. Jones has taken his place. Mr. Jones has had a year of accounting practice and is graduate of the University of Kansas. Mr. W. B. Castenholz has been appointed chairman of the Pan-American Committee of the American Society of Certified Public Accountants. Mr. Primus E. Godridge, trust officer of the Bankers Trust Co., who has been in charge of the classes in Ficuciary Accounting for the past fifteen years has resigned. His work will be taken by Mr. Chester .J. Dodge, secretary of the Surrogate's Court, New York County. An act to amend the educational law in relation to the practice of public accounting by Certified Public Accounts has been introduced in the assembly of New York by Mr. F. M. Smith. Mr. B. E. Tiffany, University of South Dakota has installed an electric posting and bookkeeping machine in the accounting laboratory, where students are to be made familiar with machine bookkeeping methods and with the use of calculating machinery.